2008
DOI: 10.1103/physrevlett.101.056403
|View full text |Cite
|
Sign up to set email alerts
|

Electronic Coherence inδ-Pu: A Dynamical Mean-Field Theory Study

Abstract: A combination of density functional theory and the dynamical mean-field theory (DMFT) is used to calculate the magnetic susceptibility, heat capacity, and the temperature dependence of the valence band photoemission spectra for -Pu. We predict that -Pu has a Pauli-like magnetic susceptibility near ambient temperature, as in experiment, indicating that electronic coherence causes the absence of local moments. Additionally, we show that volume expansion causes a crossover from incoherent to coherent electronic b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
91
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 95 publications
(97 citation statements)
references
References 26 publications
6
91
0
Order By: Relevance
“…Calculations within the framework of DFT in combination with dynamical mean field theory (DFT þ DMFT) have explained several aspects of the electronic structure of Pu (see, e.g., Refs. [80][81][82][83][84]). Nevertheless, the computational complexity of this approach made it impossible to calculate the pressure-volume phase diagram of all of the phases of Pu.…”
Section: Phase Diagram Of Plutoniummentioning
confidence: 99%
“…Calculations within the framework of DFT in combination with dynamical mean field theory (DFT þ DMFT) have explained several aspects of the electronic structure of Pu (see, e.g., Refs. [80][81][82][83][84]). Nevertheless, the computational complexity of this approach made it impossible to calculate the pressure-volume phase diagram of all of the phases of Pu.…”
Section: Phase Diagram Of Plutoniummentioning
confidence: 99%
“…Investigation of the low temperature properties of Pu has shown that the total specific magnetic susceptibility of the defects has a Curie-Weiss temperature dependence (χ ~ 1/T) [1,13,14]. It has been argued that radiation damage is either creating or uncovering local magnetic moments in Pu which may be shielded by screening in the undamaged lattice [15].…”
Section: Discussionmentioning
confidence: 99%
“…This temperature dependence has also been parameterized recently in the context of the two fluid picture [31]. In Pu the characteristic energy scale T * is estimated to be about 800K [18]. Incorporating this idea into the MEAM parameterization of the free energy, we obtained with a small modification an improved description of the physical properties of Pu, including the negative thermal expansion of the δ phase.…”
Section: Introductionmentioning
confidence: 99%
“…[14][15][16][17][18] To describe plutonium, a large number of atomic configurations are required, and valences with n f =5 and 6 have substantial weight in the ground state. This multi-determinantal mixed-valent character has been recently confirmed by resonant x-ray emission spectroscopy [19].…”
Section: Introductionmentioning
confidence: 99%